Genetic counselors' practices and confidence regarding variant of uncertain significance results and reclassification from BRCA testing - Scherr, Courtney L. (Clin Genet, 2015)
Studies indicate variant of uncertain significance (VUS) results are challenging for genetic counselors and patients, often resulting in negative patient outcomes. Genetic counselors' current practices regarding VUS are unknown. This study utilized a national survey of genetic counselors (n = 932) to examine current practices and confidence related to disclosing BRCA VUS results and reclassification information. For participants (n = 398), descriptive statistics were calculated for patient demographic characteristics, practices and confidence, and cross tabulation was used to identify participant's actions when receiving a reclassified VUS. Upon receiving a BRCA VUS report, the majority reported providing patients with information about the frequency their VUS was seen and patient ancestry, but a minority discussed DNA banking. Most were confident in their understanding of and ability to explain VUS results to patients, but felt less confident about achieving high levels of patient understanding. Upon reclassification, the majority reported calling the patient and mailing the results, but when the reclassification was deleterious the majority also met with the patient face-to-face. Given the lack of standard professional guidelines regarding informing patients about initial and reclassified VUS results, this overview provides important insight into genetic counselors' current practices and confidence.